Synthesis, Adsorption, and Recognition Properties of a Solid Symmetric Tetramethylcucurbit[6]uril-Based Porous Supramolecular Framework - Fei-Yang Tian; Rui-Xue Cheng; Yun-Qian Zhang; Zhu Tao; Qian-Jiang Zhu (Journal of Chemistry, 2020)
In this work, we reported a porous supramolecular framework (A) constructed of a symmetric tetramethylcucurbit[6]uril (TMeQ[6]) in aqueous HCl solutions; the driving force was the outer surface interaction of cucurbit[n]urils, as well as hydrogen bonding between latticed water molecules and portal carbonyl oxygens of TMeQ[6]. Adsorption experimental results revealed that the porous supramolecular framework can absorb certain fluorophore guests (FGs) to form luminescent assemblies (FG@As) by fluorescence enhancement or colour change, and some of them can respond to certain volatile organic compounds. Thus, the TMeQ[6]-based supramolecular framework could be used as a sensor for certain gas or volatile compounds.